2018
DOI: 10.3389/fncel.2018.00346
|View full text |Cite
|
Sign up to set email alerts
|

Neurocan Inhibits Semaphorin 3F Induced Dendritic Spine Remodeling Through NrCAM in Cortical Neurons

Abstract: Neurocan is a chondroitin sulfate proteoglycan present in perineuronal nets, which are associated with closure of the critical period of synaptic plasticity. During postnatal development of the neocortex dendritic spines on pyramidal neurons are initially overproduced; later they are pruned to achieve an appropriate balance of excitatory to inhibitory synapses. Little is understood about how spine pruning is terminated upon maturation. NrCAM (Neuron-glial related cell adhesion molecule) was found to mediate sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…GWAS data show that NCAN is one of the common variants that are significantly associated with BPI risk [21,22,46,47]. NCAN is a proteoglycan that is involved in cell adhesion and neuronal migration, processes that are pivotal during neurodevelopment [42][43][44][45]84]. Our findings are relevant in the context of the hypotheses and previous evidence for the neurodevelopmental roots of the disease biology of BPI [13,85].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…GWAS data show that NCAN is one of the common variants that are significantly associated with BPI risk [21,22,46,47]. NCAN is a proteoglycan that is involved in cell adhesion and neuronal migration, processes that are pivotal during neurodevelopment [42][43][44][45]84]. Our findings are relevant in the context of the hypotheses and previous evidence for the neurodevelopmental roots of the disease biology of BPI [13,85].…”
Section: Discussionmentioning
confidence: 57%
“…1b). NCAN is a proteoglycan that is a component of the neuronal extracellular matrix that is expressed during the modeling and remodeling of neuronal tissue and modulates neural adhesion and migration [42][43][44][45]. Genome-wide association studies have implicated common variation in NCAN as a risk for BPI [21,22,46,47].…”
Section: Analysis Of Protein-protein Interaction (Ppi) Networkmentioning
confidence: 99%
“…Genetic studies in humans revealed that the variation of NCAN, a gene encoding PNN component protein neurocan, is a common risk factor for schizophrenia and bipolar disorder (MĂŒhleisen et al, 2012;Oruč et al, 2012;Schultz et al, 2014). Neurocan has also been shown to regulate brain development, dendritic spine remodeling and the function of GABAergic interneurons (Zhou et al, 2001;Mohan et al, 2018;Sullivan et al, 2018). The assembly and function of PNNs are disrupted when these component proteins are hydrolyzed or the structures are destroyed, which could ultimately lead to negative consequences and pathophysiology of neuropsychiatric disorders (Wen et al, 2018;Testa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During postnatal development, neurocan assembles around processes, dendritic spines, and soma of pyramidal neurons. Neurocan has been shown to inhibit Sema3F-mediated spine retraction in cortical neurons in culture by binding NrCAM and inhibiting its function within the Sema3F holoreceptor ( Figure 4B ; Mohan et al, 2018 ). Neurocan also binds to the Ig2 domain of NCAM at the EphA3 binding site, inhibiting the repellant response to EphrinA5 exhibited by remodeling basket cell terminals ( Sullivan et al, 2018 ).…”
Section: Perineuronal Net Proteins Stabilize Synapses Bind Neural Admentioning
confidence: 99%